Crc Regulates Succinate-Mediated Repression of Mineral Phosphate Solubilization in Acinetobacter sp. SK2 by Modulating Membrane Glucose Dehydrogenase - Bharwad, Krishna; Ghoghari, Niharika; Rajkumar, Shalini (Frontiers in Microbiology, 2021)
The plant growth promoting Acinetobacter sp. SK2 isolated from Vigna radiata rhizosphere was characterized for mineral phosphate solubilization (MPS). To understand the contribution of the membrane glucose dehydrogenase (mGDH) and soluble glucose dehydrogenase (sGDH) in glucose oxidation and mineral phosphate solubilization (MPS), insertional inactivation of the corresponding genes was carried out. The disruption of mGDH encoding gene gdhA resulted in complete loss of mGDH activity which confirmed its role in periplasmic glucose oxidation and gluconate mediated MPS phenotype. The inactivation of sGDH encoding gene gdhB resulted in loss of sGDH activity which did not alter MPS or mGDH activity. Thus it was also concluded that the sGDH was dispensable in gluconate mediated MPS. Supplementation of succinate in glucose containing medium suppressed the activity of mGDH (and sGDH) and therefore repressed MPS phenotype. The catabolite repression control protein (Crc) of Pseudomonas was implicated in Acinetobacter sp. for a similar function in presence of preferred and non-preferred carbon sources. To understand the regulatory linkage between Crc and genes for glucose oxidation, crc mutants were generated. Inactivation of crc resulted in increased activity of the mGDH in glucose+succinate grown cells indicating derepression. An increase in phosphate solubilization up to 44 % in glucose+succinate grown crc- compared to glucose grown cells was recorded which was totally repressed in wild-type strain under similar conditions. It is therefore proposed that in Acinetobacter sp. SK2, Crc is involved in the succinate provoked repression of MPS phenotype. The gene expression data indicated that Hfq may also have a regulating role in preferential utilization of carbon source by perhaps modulating Crc-Hfq functionality. Vigna radiata plants inoculated with the wild-type improved both root and shoot length by 1.3-1.4 fold. However, crc inactivated strains increased the root and shoot length by 1.6 folds, compared to the uninoculated controls. In mimicking the soil condition (in presence of multiple carbon sources eg; succinate along with glucose), the crc inactivated strain of phosphate solubilizer performed better in supporting the growth of Vigna radiata in pot experiments.